Decentralized marketplace for digital assets empowered by smart contracts - Garg, Astha (Nanyang Technological University, 2023)
The rise of Non-Fungible Tokens (NFTs) has been nothing short of phenomenal. With the total value of international NFT transactions exceeding 11 billion USD, it is clear that NFTs have emerged as a new asset class that is here to stay. While NFTs have provided a new way for creators to monetize their digital assets, the lack of liquidity and high price barriers have prevented small investors from participating in the market. This is where fractionalized NFTs come in, offering investors the ability to own a piece of a valuable NFT at a fraction of the cost. NFT marketplaces are the backbone of the NFT ecosystem, providing a platform for creators to showcase and sell their NFTs. While platforms like OpenSea have emerged as the market leader, they have their limitations. These platforms do not allow the fractionalization of NFTs, which restricts access to high-value NFTs. Additionally, poor user experience and the lack of social integration are major barriers to interaction between community members. This paper aims to present NFT Nook, a decentralized marketplace that addresses these shortcomings. NFT Nook enables the fractionalization of NFTs, allowing small investors to participate in the market. The platform also prioritizes user experience and social integration, providing users with a seamless and engaging experience. The platform is built on the Ethereum blockchain, providing users with the security and immutability that is inherent to blockchain technology. Before eliciting requirements, the current marketplaces were extensively researched to understand their merits and limitations. To foster a sense of community, social elements such as following, supporting creators through donations, and commenting have been incorporated. Additionally, fractionalized NFTs are generated and marketed to offer a comprehensive NFT platform. The platform prioritizes user interface and user experience, resulting in a seamless and enjoyable experience for users as they explore and engage with various features. Overall, NFT Nook represents a significant step forward for the NFT marketplace. By addressing the shortcomings of existing platforms and offering new features, it provides valuable tools for building a strong community of supporters around a creator's work. With these features, NFT Nook can offer a unique value proposition to creators who prioritize building a strong community and fostering deeper connections with their supporters. As such the platform has the potential to democratize the NFT market and bring new participants into the ecosystem.